Onveilig,onvoldoende, oncomfortabel : parkings langs de autowegen levensgevaarlijk! - Peeters, Tom; Moreels, Frank; Baes, Walter (Antwerpen: BTB; ABVV, 2012)
"Tom Peeters, Frank Moreels, Walter Baes... et al."